Strengthening Islamic Religious Education for Muslim Minorities at SMP Negeri 1 Larantuka East Flores - Fihris; Kasan Bisri; Muhammad Noor Taufik (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This research aims to find out the efforts to strengthen Islamic Religious Education as well as the problems and solutions to efforts to strengthen Islamic Religious Education for Muslim minorities carried out at SMP Negeri 1 Larantuka East Flores. Design/methods/approach – The research method used in this study is Qualitative Research, which is a series of activities related to the method of collecting information through observations, interviews, and documentation. Findings – The study results revealed that efforts to strengthen Islamic Religious Education for minority Muslims at SMP Negeri 1 Larantuka Flores Timur comprised 1) Spiritual Development; 2) Spiritual Strengthening; 3) Iftar Gathering; and 4) Halal bi Halal. The problems faced in the activities of strengthening Islamic Religious Education at SMP Negeri 1 Larantuka Flores Timur included internal factors, lack of support from the teachers at SMP Negeri 1 Larantuka Flores Timur, and inadequate school facilities for indoor activities. Research implications/limitations – Despite the study's significant contribution to the religious strengthening program for minority Muslim students in schools, this research still has some limitations, such as the limitation of the research site that was only one school. Originality/value – This research has an important meaning in providing discourse and discourse on religious strengthening activities or programs at SMP Negeri 1 Larantuka Flores Timur. The findings of this study have emphasized that there is still a discriminatory attitude towards minority Muslim students in schools. Therefore, PAI teachers in Muslim minority schools are expected to pay more attention to these minority Muslim students.